Brain structural differences between fibromyalgia patients and healthy control subjects: a source-based morphometric study - Elijah Agoalikum; Hongzhou Wu; Benjamin Klugah-Brown; Michael Maes (Scientific Reports)
Abstract Fibromyalgia (FM) is a chronic pain condition that predominantly affects women. Evidence implies that FM is associated with dysfunction of the central nervous system (CNS). In this study, we investigated the structural differences between FM patients and healthy control (HC) subjects using a multivariate approach. Source-based morphometry (SBM) was applied to structural magnetic resonance imaging (sMRI) data consisting of 20 FM patients (46.4 ± 12.5), and age and gender-matched 20 HC subjects (42.1 ± 12.5). SBM revealed greater grey matter volume (GMV) in the bilateral thalamus in FM patients. Conversely, lower GMV was found in the bilateral putamen, bilateral pallidum, right cerebellum, right calcarine, right amygdala, and bilateral insula in FM patients. Further analysis indicated that grey matter deficits in the pallidum were significantly associated with pain catastrophizing, pain magnification, rumination, and feelings of helplessness, suggesting a link between structural brain changes and clinical pain metrics. These findings provide new insights into the neurobiological underpinnings of FM, highlighting the role of specific brain regions in pain processing and emotional regulation. The results underscore the potential for targeted therapeutic interventions that address both the neurobiological and psychological aspects of FM, paving the way for more effective management strategies for this complex condition.